MANAJEMEN ORGANISASI SISWA INTRA SEKOLAH (OSIS) UNTUK MENINGKATKAN KINERJA SEKOLAH PADA MADRASAH TSANAWIYAH ANWARUL HASANIYYAH - Ahmad Fikri Azhari; Muhammad Aminullah; Muhammad Ghani; Muhammad Hidayat; Syahrani Syahrani (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
The aim of this research is to describe the performance of the OSIS at MTs Anwarul Hasaniyyah. To describe organizational management in improving OSIS performance at MTs Anwarul Hasaniyyah. In order to find out the supporting and inhibiting factors in improving the performance of the OSIS at MTs Anwarul Hasaniyyah. This research is qualitative field research. The method used is a qualitative method with a qualitative descriptive design with data collection techniques through observation, interviews and documentation. Next, data analysis was carried out using descriptive analysis. The results of the research show that: the performance of the OSIS at MTs Anwarul Hasaniyyah has improved compared to before, seen from the enthusiastic participation of OSIS children in carrying out OSIS activities. But there are still some OSIS students who are lazy about participating in OSIS activities. Organizational management can clearly be seen from the organizational structure, where OSIS administrators have their respective duties and responsibilities. Through the management of this organization, they receive guidance and direction from the Head of the Madrasah, Deputy Head of Student Affairs, and OSIS Supervisor. The supporting factors are teachers, parents, budget, facilities and infrastructure. Meanwhile, the inhibiting factors are the lack of organizational experience, the student council administrators do not understand their work and peers.